Epistemology of Islamic Integralism as a Solution to Building a Global Civilization: The Thoughts of Mahzard and Agus Purwanto - Alifia Zuhriatul Alifa; Muhammad Isa Anshari; Ahmad Barizi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The study aims at studying the concept of Islamic integralism according to Armahedi Mahzar and also the epitymology of the Islamic science according to Agus Purwanto in an attempt to create the paradigm of Islamical integralism in building a global civilization. This research includes a type of library research that analyzes some literature based on the study of Islamic integralism. From the results of the research, the research found that Armahedi Mahzar offers the concept of universal integralism known as the tauhid paradigm if it emphasizes its divine aspekon, and the wahdatiyyah paradigm when it emphasises its integrity aspekon. And Agus Purwanto, proposing a new approach in the construction of science in Islam, namely Islamic Science based on the Qur'an as the first foundation in the building of science. From the thought of the two was born the Concept of the Paradigm of Islamic Integralism as an attempt to build a global civilization that believes that Islamic Sciences must be source and based on Wayhu and Islamic science as thanksgiving to God so that technology should be combined with gratitude to Allah SWT.